Pengembangan Multimedia Interaktif Aku Melihat karena Cahaya pada Siswa Kelas V-A SN Demangan 2 Bangkalan - Andini Wulan Cahyani; Isna Ida Mardiyana (Mataram University, 2026)
This study aimed to develop the Aku Melihat karena Cahaya Interactive Multimedia for fifth-grade elementary students and determine its validity, effectiveness, and attractiveness. The study was motivated by the limited availability of interactive multimedia on the topic of seeing because of light that can be accessed flexibly across various digital devices, highlighting the need for the development of more accessible and interactive learning media. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analyze, Design, Develop, Implement, and Evaluate stages. The research was conducted at SDN Demangan 2 Bangkalan during the 2025/2026 academic year. The subjects included one material expert, one media expert, one instructional design expert, three students in the one-to-one trial, eight students in the small-group trial, and twenty-eight students in the field trial. Data were collected through interviews, observations, questionnaires, tests, and documentation. The results showed that the multimedia achieved validity scores of 93.3% from the media expert, 87.5% from the material expert, and 95.45% from the instructional design expert, indicating a very valid category. The readability test obtained 91.11%, categorized as very feasible. In the field trial, the multimedia achieved an attractiveness score of 93%, student activity reached 92% (very effective), and classical learning mastery reached 89%, exceeding the minimum criterion of 75%. Therefore, the Aku Melihat karena Cahaya Interactive Multimedia is valid, attractive, and effective for supporting science learning on the topic of seeing because of light in elementary schools.